POTENTIAL OF GREEN FORAGE TO RUMINANT ANIMALS IN DEEP COCONUT PLANTATION IN HUAMUAL DISTRICT, SERAM ISLAND - Nawaly, Hendriko; Eoh, Marna; Patty, Christian Willem (RUMPHIUS, 2023)
This research aims to determine the potential for forage for ruminant livestock under coconut trees in Huamual District, West Seram Regency. Three villages, namely Ariate Village, Loki Village and Luhu Village, were selected using the pruple sampling method. This research uses a survey method through direct observation and measurements in coconut plantation areas. This research was carried out using the dry weingh rank method to measure botanical composition, to calculate forage production using the Actual Weight Estimate method and measuring carrying capacity using the Voisin (y-1) s = r formula. The results of this research show that the botanical composition of the forage found in the area under coconut trees is 14 species consisting of 7 species of grass, namely paspalum (Paspalum distichum), charred grass (Sporobolus indicus), Bermuda grass (Cynodan dactylon), Bengal grass (Panicum maximum), carpet grass (Axonopus compresus), buffalo grass (Paspalum conjigatum), field puzzle grass (Cyperus rotundus) 63.49%, 5 weed species namely Chinese purslane (Euphorbia prostrate), lizard fern (Cyclosorous aridus), minjang (Chormolaena odorata ), flower fern (Lygodium flexuosum), galunggang (Sida acuta) 28.10% and 2 species of butterfly pea legume (centrosema), calopo (calopogonium) 9.13%. This shows that the most dominant grass is paspalum grass (paspalum distichum), forage production has a fresh weight of 3847.86 tons/year and the carrying capacity in the area under coconut trees is 0.441 Ha/UT or 2.27 UT/Ha. With a total area of 1211 coconut trees, it can be estimated that it can accommodate 534,051 and the data on the ruminant livestock population in Huamual sub-district is 710,949 UT/year.